PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA POKOK BAHASAN PENYUSUTAN AKTIVA TETAP DENGAN METODE MENJODOHKAN KOTAK - Winarti Winarti (Dinamika Pendidikan)
The low students’ activeness level in the teaching and learning process will influence students’ achievement. Choosing the varied and appropriate learning method is very important for the success of teaching and learning process. The purpose of this study was to enhance the students’ activeness and students’ learning outcomes at the topic of Fixed Assets Depreciation by using cooperative learning with match box method, especially for students of class XI AK 2 at SMK N 2 Blora. It was a classroom action research. The methods of the study were observation and evaluation. The results of the research showed that match box method can increase students’ activeness. Students’ activeness was only 71.05% at the beginning and after using the match box method, it rose up to 84.21% and was successful to improve students’ learning outcomes because students’ learning completeness rose from 28.95% to 65.79% .